A comparison of HIV related advice in genitourinary medicine clinics with different histories. Issue 4 (August 1996) - Hope, V D; MacArthur, C
Abstract : OBJECTIVES: To examine attendees reported experiences of health advice provision in genitourinary (GUM) clinics with different histories. DESIGN: A self-completed anonymous questionnaire was distributed at five clinics in the West Midlands Region of the United Kingdom. RESULTS: 297 of the 360 attendees approached returned completed questionnaires; 89.5% reported receiving health advice, 86.4% found all of this easy to understand and 10.4% wanted more advice. However, 33.9% received no advice on either HIV or safer sex. Those attending new clinics, set up since the HIV pandemic, were more likely than those attending older clinics, to have understood the advice given, to have had advice on both HIV and safer sex, and less likely to have wanted more advice. Among those attending with a concern about HIV, 14% claimed to have received no advice on either HIV or safer sex; with no difference between old and new clinics. For those attending with reasons particularly relevant to receiving HIV related advice, but not with a concern about HIV, 40% claimed to have received neither HIV nor safer sex advice. In this sub-sample, those attending new clinics were more likely to have received advice on HIV as well as safer sex, and less likely to want more advice. CONCLUSIONS: The results indicate that the provision of advice needs to be reconsidered, particularly in older clinics.